Importance of trauma‐related fear in patients with irritable bowel syndrome and early adverse life events. Issue 9 (17th June 2020) - Rahal, Harman; Videlock, Elizabeth J.; Icenhour, Adriane; Shih, Wendy; Naliboff, Bruce; Gupta, Arpana; Mayer, Emeran A.; Chang, Lin
Abstract: Background: Although early adverse life events (EALs) are prevalent among patients with irritable bowel syndrome (IBS), the impact of fear or dissociation experienced during the trauma has not been evaluated. We investigated the prevalence of fear at the time of trauma and its association with IBS status among individuals with early‐life trauma before the age of 18. Methods: Among participants with ≥1 EAL, association of fear and dissociation with IBS status was determined with logistic regression, and improvement in prediction of IBS over ETI score alone was determined with the likelihood ratio test. Controlling for age, sex, and IBS status, we then examined the association of each EAL with reported fear. Key Results: Compared to healthy controls (HCs), IBS subjects reported a higher prevalence of fear (60.4% vs 36.2%, P < .0005) and dissociation (23.5% vs 13.0%, P < .0005) at the time of EAL. Fear, but not dissociation, improved prediction of IBS over the total number of EALs (odds ratio = 2.00, P < .0001). Conclusions and Inferences: This study highlights the importance of EAL‐related factors such as fear in addition to the presence or absence of EALs in IBS pathophysiology. Abstract : Early adverse life events (EALs) are a known risk factor for the development of irritable bowel syndrome (IBS). Here we show that among participants with one or more EAL, fear at the time of the EAL adds to the risk of IBS associated with the total number of EALs. Our findings suggest that in addition to the number of EALs, EAL‐related factors such as fear, may contribute to IBS pathophysiology.